Bentuk Emosi Bullying dan Korban Bullying di Sekolah (Studi Kasus SMP Negeri 27 Medan) - Nurul Syavika; Rahmi Pratiwi; Dika Sahputra; Muhammad Putra Dinata Saragih; Annisa Arrumaisyah Daulay (Universitas Batanghari Jambi, 2023)
Bullying is one of the factors that cause emotional tendencies. One of the impacts of bullying is that various forms of emotions are formed in children, both to the bullying or the victim (victim). The research strategy is this case study which aims to obtain information about the emotional form of Bullying and Victims (Victim) in the form of student behavior. Based on the results of this study, the form of emotion caused by bullying behavior is that initially the perpetrator has the characteristics of wanting to show himself and get the attention of others, but when the perpetrator sees his friend who has more abilities than him, the form of emotion that is generated is hate. The hatred that is generated actually hurts and causes bullying behavior. Vice versa, a friend who was bullied (Victim) has a high temperament and stubborn characteristics, so that the emotions that arise are aggressive, impulsive and willing to take revenge on friends who hurt him. To follow up the emotional form of Bullying and Victim Behavior (Victim) it requires the role of Counseling Guidance Teachers in schools. Counseling teachers must make service programs about preventing bullying in schools, such as group guidance services, group counseling, classical guidance and provide individual guidance to behavior or victims involved in bullying cases. BK teachers can also use technological sophistication to run programs such as using animated videos related to bullying as well as providing the impact caused by bullying or victim behavior (Victim).